Sumber kecemasan dan strategi koping remaja pada masa pandemi COVID-19 - Valentina, Tience Debora; Nurcahyo, Firmanto Adi; Astiti, Dewi Puri (Universitas Brawijaya, 2023)
This research was conducted to explore the source of anxiety and coping strategy of youth during the COVID-19 pandemic in Indonesia. A qualitative survey was conducted online with 365 young people aged 15-23 year. Six themes arise in this study that show sources of anxiety of young people, namely: a) fear of being infected with the COVID-19, b) uncertainty about the future, c) social relation problems, d) academic-related anxiety, e) family economic problems, f) exposure to information on cases of COVID-19 infection. We also found eight coping strategies to deal with anxiety, namely religious coping, active coping, making meaning, seeking emotional support, optimism, avoidance, emotional regulation, and exercises. The findings implied that young people develop religiosity and in combination with other coping strategies to endure the unprecedented outbreak of COVID-19. This finding implies that psychological interventions should address religious coping to help young people to cope with various sources of anxiety during stressful life events such as the COVID-19 pandemic.